Educação, regionalização do ensino e ambiente: exemplo de Roraima - Silva, Wilma Marinho Craveiro da (2015)
The present dissertation is a succinct portrait of the education in Brasil, starting by the important aspects of the colonial period, with the introduction of the education by the Jesuits priests. From this point the dissertation makes a script which discusses education during the imperial period until de decade of 1990. This historical approach is important in order to give the orientation inside the context of education as critic reflection and transforming agent of the society – these aspects are discussed along the dissertation. Together with this historical context, parallel intercrossing lines are traced in order to approach the education in Roraima, with census information and critical discussion. In this context the dissertation also makes analogies between the regional education and environmental education in Roraima, two educational cleavages with the same normative roots – the norms of the education is approached all along the dissertation as the aspect that gives the north of the educational process in Brasil, which one (the normative process per se) is the antithesis of the reflexive and critic education, but difficult to adopted in various Brasilian regions. The aspects regional education and environmental education are discussed in terms of the official education in Roraima.